Spatiotemporal Modeling of Soil Erosion Under Agricultural Expansion in the Amravati Basin, India Using RUSLE–GIS - Vikram Agone; Hemlata Agone (International Journal of Land, 2026)
Agricultural expansion and soil erosion are important environmental issues in areas where agriculture is a major source of livelihood. This study analyzes the spatial and temporal patterns of soil erosion in the Amravati Basin of Maharashtra and evaluates the impact of agricultural expansion using the Revised Universal Soil Loss Equation (RUSLE) integrated with Geographic Information System (GIS) techniques. Multi-source data, such as satellite imagery, rainfall records, soil characteristics, and topography data, were used to determine the RUSLE factors (R, K, LS, C, and P) and generate soil erosion risk maps for 2014, 2024, and the year 2034. The results of the land use/land cover (LULC) change detection indicated a significant decrease in forest cover and an increase in agricultural land cover, which was significantly correlated with high soil loss areas (> 100 t/ha/year; r = 0.94). The prediction analysis shows that there will be a sharp decline in low-erosion areas and a frightening increase in high-erosion classes by 2034, especially in upland croplands and on deforested slopes. The results indicate that concerted efforts for conservation should be conducted, such as contour farming, vegetative barriers, agroforestry, and the incorporation of soil conservation mechanisms in regional land-use plans. This study provides valuable information to policymakers and land managers to develop sustainable agricultural and environmental management practices.
Keywords: GIS; RUSLE; agricultural expansion; soil conservation; soil erosion; spatial modeling